Integrated stratigraphic study of the Cretaceous petroleum-potential succession, Sulaimani area, Kurdistan, Iraq - Al-Qayim, Basim; Hussein, Shireen; Qader, Fouad M.; Bestoon, Salim H. Al-Hakari; Shukor, Bestoon; Sardar2, Ziryan; Ahmed2, Dler; Abdullah, Hawar (Sulaimani Journal for Pure and Applied Sciences, 2016)
The Cretaceous sequence of Kurdistan Region of northeast Iraq form an important petroleum system in housing potential source rocks such as the Balambo, Sarmord and Shiranish Formations. It also includes an important reservoir rocks supplied with good secondary porosity such as the Qamchuqa and Kometan Formations. This study examined surface and subsurface sections of these units from Sulaimani area of Kurdistan region of northeast Iraq using stratigraphic analysis, microfacies investigations, lithostratigraphic correlation in an attempt to characterize these units at this area and to give an insight regarding the stratigraphic architectural impact on the development of their petroleum system. Microfacies analyses show the occurrences of deep to shallow marine facies. It ranges between basinal foraminiferal- Oligostiginal grainstone to wakestone (Balambo, Sarmord, Kometan, Shiranish, and parts of the Tanjero Formations) to bioclastic -foraminiferal packstone to wackestone of the Qamchuqa Formation. The Dolostone part of the Qamchuqa Formation is characterized by medium to coarse crystalline planar-e to planar-s type mosaic. The Late Cretaceous units of the Kometan, Shiranish, and Tanjero Formations in both outcrop and neighboring subsurface sections, show little stratigraphic differences within the study area from elsewhere in Kurdistan Region. The Early Cretaceous units of the Balambo, Sarmord and Qamchuqa Formations (which are the focus of this study), however, show lateral and vertical stratigraphic variations in lithology and thicknesses in both northward and westward directions. The basic difference is the change of the deep marine Oligostiginal marly limestone of the Balambo Formation into the dolomitized platform carbonates of the Qamchuqa Formation in both directions. This lateral changes passes through a transitional zone of interfingering relation, which is up to 15Km in width. This zone plays an important role in developing the Cretaceous petroleum system of the area.
Keywords: Cretaceous; Kurdistan,Stratigraphy; Iraq,Petroleum System